2015
DOI: 10.1097/apo.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-linking

Abstract: Corneal collagen cross-linking (CXL) has been shown to slow down or stop the progression of keratoconus. In addition, CXL has been applied in cases of corneal ectasia. Recent reports of the use of CXL in cases of infectious keratitis have generated further interest in this treatment modality. This review discusses the principle, clinical uses, and complications associated with CXL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Corneal collagen crosslinking (CXL) is an established treatment for slowing down or stopping disease progression in keratoconus and corneal ectasia. [ 10 ] While a majority of studies have reported outcomes of CXL in primary keratoconus, few publications have shown encouraging outcomes with CXL in post-refractive surgery keratectasia. [ 5 , 9 , 11 ] Unlike previous studies that used the epithelium-off protocol for CXL, we performed CXL in our patients with or without flap lift.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal collagen crosslinking (CXL) is an established treatment for slowing down or stopping disease progression in keratoconus and corneal ectasia. [ 10 ] While a majority of studies have reported outcomes of CXL in primary keratoconus, few publications have shown encouraging outcomes with CXL in post-refractive surgery keratectasia. [ 5 , 9 , 11 ] Unlike previous studies that used the epithelium-off protocol for CXL, we performed CXL in our patients with or without flap lift.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Overall, with rarely associated risks, the safety of corneal cross-linking is well established when performed within certain parameters. 2 Previously outlined contraindications for CXL include active infectious keratitis and pregnancy. 3 In addition to these conditions, a 400 µm minimum corneal thickness is a suggested criterion for determining procedure eligibility.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Other risks include edema, infectious keratitis, corneal perforation, and corneal scarring. 12 An effective CXL procedure not requiring epithelial removal (epi-on CXL) would be safer and less disruptive for the patient.…”
Section: Introductionmentioning
confidence: 99%